Give me back life and allow me to live – Do not destroy me in fire: Environmental and social impacts of fires in the Northern region of Brazil in the light of International Environmental Law - Gonçalves, Marcus Fabiano; Oliveira, Terezinha Azevedo (Seven Editora, 2024)
This article has the objective of analyze the environmental and social impacts of fires in the Northern region of Brazil, focusing on the spatial scope of the state of Rondônia, from the perspective of International Environmental Law. To this end, methodologically, the study will be supported by bibliographical research with references on the subject with a view to problematizing the effectiveness of Brazilian and international environmental standards in combating illegal fires, which bring devastating consequences for the environment and society in general. The inestimable value of the northern region of the country – in which the Amazon Forest is located – can be seen due to the richness of its biodiversity. It is considered that the regulations to combat environmental and social damage caused by fire have not been efficient. In this way, the importance of the International Environmental Law for systematizing Brazilian environmental legal protection standards is understood. Only through environmental education inserted in the various social spheres is it possible to change the mentality of society in the sense of attributing value and importance to the environment in which they live. DOI:https://doi.org/10.56238/sevened2024.007-009